The role of the Central Bank in preventing the liquidity crisis in recent years in Afghanistan - Bashiri, Abdul Basit; Lindrianasari, Lindrianasari; Dharma, Fitra (Goodwood Publishing, 2023)
Purpose: This study aims to examine Afghanistan’s financial situation, with particular emphasis on the role of the central bank in addressing the ongoing liquidity crisis. It seeks to analyze the structural and operational challenges faced by Afghan banks in maintaining adequate funds and fulfilling their obligations without incurring significant financial losses. Methodology: This study employed a mixed-method approach, combining document analysis and qualitative descriptive research. Primary data were obtained from reports of international organizations, such as the UNDP and the World Bank, as well as official submissions from the Da Afghanistan Bank (DAB). Targeted sampling was used to select participants and informants directly associated with central banking, financial institutions, and relevant government departments. Field observations and monitoring of banking operations were conducted to provide context. Results: The findings reveal that Afghan banks are experiencing severe liquidity shortages caused by declining economic activity, restricted access to cash, weak institutional capacity, and a diminished public trust in the financial system. The political transition following the Taliban takeover further aggravated the crisis, leaving several banks on the brink of insolvency and increasing the risk of systemic bank failure. Conclusions: This study concludes that Afghanistan’s liquidity crisis is a structural issue that requires comprehensive policy responses. Strengthening the supervisory role of the central bank, rebuilding public confidence, and ensuring sustained access to capital are critical measures to stabilize the financial sector and prevent its collapse. Limitations: This study is limited by its reliance on secondary data and restricted field access due to political instability and security risks. Contribution: This study enriches the post-conflict financial governance literature by emphasizing the importance of central banking policies and institutional trust in stabilizing fragile economies and preventing financial collapse.